Factors Associated with Access to the General Curriculum for Students with Intellectual Disability - Meagan Karvonen; Claudia Flowers; Shawnee Y. Wakeman (Arizona State University, 2013)
Beginning in 1997, federal legislation required schools provide access to academic curricula to students with intellectual disability.  The extent of such access for students with significant intellectual disability currently is not known.  This study examined access (defined by scope and intensity of content instruction and depth of knowledge) provided to students with significant intellectual disability, and relationship between curriculum access and a set of teacher and student characteristics.  A survey of 644 teachers from nine states found that these students, on average, were exposed to 17 out of 27 English language arts strands and 10 out of 16 math strands.  Canonical correlation analyses suggested that students' symbolic communication level had the strongest association with students' access.  Cluster analysis suggested students experience three types of access to English language arts and four types of access to math instruction, and the cluster groups significantly differed by teacher and student variables. These findings suggest several policy and practice actions to better support meaningful participation in the general education curriculum among students with intellectual disabilities.